Clinical supervision in the helping professions : a practical guide - Corey, Gerald (Alexandria,VA: American counseling Assosciation, 2021)
"The field of supervision is a rapidly emerging specialty area in the helping professions. In the past, supervisors often learned how to supervise based on their own, and often limited, experiences when they were supervisees. At one time few professional standards specifically addressed supervision practices, and separate courses in supervision were rare. Today, the trend is toward including a course in supervision in graduate programs in the helping professions, especially in doctoral programs. If there is not a separate course, topics of supervision are frequently incorporated into one or more courses. In addition, state licensing and certification boards are increasingly requiring formal training in the area of supervision as a part of the licensing and certification process. The result of these trends is that in order to practice as a supervisor it is mandatory to complete course work or take continuing education workshops in supervision and to show evidence of competence not only in skills and techniques but in supervisory processes and procedures. This book provides a practical guide to becoming a supervisor. Our aim has been to make it reader-friendly, informative, interesting, practical, personal, encouraging, and challenging. We address topics essential to becoming an effective supervisor, with emphasis on helping new supervisors acquire the knowledge and skills necessary to supervise others in a variety of settings. We believe one of the best ways to learn how to supervise is for new supervisors to reflect on what they have learned from their own supervision"--
Includes bibliographical references and index.
Keywords: Clinical psychologists -- Supervision of; Counselors -- Supervision of; Psychotherapists -- Supervision of; Health services administration